Should I stay or should I go now? Temporary migration: a survey and questions for New Zealand - Chris Nixon; Chris Nees (New Zealand Institute of Economic Research (NZIER), 2005)
In this paper we examine the issues and debates surrounding temporary migration. This is a critical issue, since to attract high quality human capital, New Zealand must compete in the global market place. By examining the economic context in which temporary migration takes place we will gain a clearer understanding of the factors which influence this form of migration and the reasons behind the changes in the composition of migration.
Keywords: 330; Internationale Arbeitsmobilität; Migrationspolitik; OECD-Staaten; Neuseeland